GPGP-Vc - Alvarez, Laura (SciLifeLab Serve, 2026)
Shiny app for exploration of the Genome-wide PeptidoGlycan Profiling dataset of Vibrio cholerae mutant library. Access to this app is password protected while it is under peer review.